Boosting Akt Pathway by Rupatadine Modulates Th17/Tregs Balance for Attenuation of Isoproterenol-Induced Heart Failure in Rats - Ahmed, Lamiaa A.; Mohamed, Ahmed F.; Abd El-Haleim, Enas A.; El-Tanbouly, Dalia M. (Frontiers in Pharmacology, 2021)
Disruption of Th17/Treg homeostasis plays a crucial role in governing the immune response during myocardial fibrosis and its progression to heart failure. The present study aimed to assess for the first time the possible protection afforded by rupatadine (RUP) against isoproterenol (ISO)-induced heart failure (HF) in rats. It also explored the role of PI3k/Akt as a possible mechanistic pathway, through which RUP could modulate Th17/Treg balance to display its effect. ISO (85 and 170 mg/kg/day) was injected subcutaneously for 2 successive days, respectively and RUP (4 mg/kg/day) was then given orally for 14 days with or without (PI3K/Akt inhibitor), wortmannin. RUP succeeded to completely ameliorate ISO-induced cardiac dysfunction as demonstrated by improvements of electrocardiographic and echocardiographic measurements. Moreover, RUP prevented the marked elevation of PAF and oxidative stress in addition to Th17 promoting cytokines (IL-6, IL-23 and TGF-β). Accordingly, RUP prevented Th17 stimulation or expansion as indicated by increased Foxp3/RORγt ratio and decreased production of its pro-inflammatory cytokine (IL-17). RUP treatment mitigated ISO-induced activation of STAT-3 signaling and the imbalance in p-Akt/total Akt ratio affording marked decrease in atrogin-1 and apoptotic biomarkers. Finally, this therapy was effective in averting cardiac troponin loss and reverting the histological alterations as assessed by myocardial fibrosis and hypertrophy grading. Contrariwise, co-administration of wortmannin mostly attenuated the protective effects of RUP affording more or less similar results to that of ISO-untreated rats. In conclusion, RUP could be an effective therapy against the development of ISO-induced HF where PI3K/Akt pathway seems to play a crucial role in its protective effect.